2009
DOI: 10.1378/chest.08-2288
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study To Examine the Effects of Smoking Cessation on Serum Markers of Inflammation in Women at Risk for Cardiovascular Disease

Abstract: Background The links between smoking, inflammation, and cardiovascular disease (CVD) are well-established. Several studies demonstrate that quitting smoking reverses the risk of coronary heart disease within five to ten years. However, the immediate effects of quitting smoking on inflammatory biomarkers associated with CVD risk are not well described. Methods In this pilot study, we examined a panel of circulating inflammatory biomarkers associated with CVD in ‘at risk’ women during the smoking cessation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…In addition, hsCRP is associated with atherosclerotic processes40 and thus may also be directly involved in cardiovascular injury. The high sensitivity of this test, as indicated by significant differences via secondhand smoking exposure and consistent results for different indices of tobacco exposure in ELSA‐Brasil and across other studies,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 41 highlights hsCRP as a favorable marker for monitoring hazardous health effects of tobacco exposure.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, hsCRP is associated with atherosclerotic processes40 and thus may also be directly involved in cardiovascular injury. The high sensitivity of this test, as indicated by significant differences via secondhand smoking exposure and consistent results for different indices of tobacco exposure in ELSA‐Brasil and across other studies,5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 41 highlights hsCRP as a favorable marker for monitoring hazardous health effects of tobacco exposure.…”
Section: Discussionsupporting
confidence: 73%
“…These studies have generally shown higher levels of hsCRP among current and former smokers compared with nonsmokers5, 6, 9, 10, 12, 13, 14, 15 and decreased levels after smoking cessation, albeit slower than systolic blood pressure and total cholesterol and LDL‐C 8, 11, 12. Calculating the probability of CAC onset following smoking exposure in the Heinz Nixdorf Recall study also demonstrated that onset of CAC was expedited by 10 years among current smokers and 5 years among former smokers compared with never smokers 16.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there is an increasing number of reports where smoking cessation may temporarily elevate the risk for type 2 diabetes, 51 even smaller changes can be clinically significant and serve as a motivator for the participants. 64 …”
Section: Smoking Cessation/exercise Improve Cvd Biomarkersmentioning
confidence: 99%
“…The removal of tobacco smoke results in the elimination of the deleterious effects of the thousands of chemicals contained in cigarette smoke. Within weeks of cessation endothelial function, coagulation parameters, carboxyhemoglobin levels, lipoproteins, proinflammatory agents, and inflammatory biomarkers decline and circulatory function improves dramatically [29,30]. For the patient with CAD, the result is a highly significant reduction in the likelihood of progression or complication of existing disease, and there is a significant reduction in the possibility of hospital readmission, morbidity, and all-cause mortality [31••].…”
Section: The Cardiovascular Benefits Of Smoking Cessationmentioning
confidence: 99%